A three-dimensional active biochar for sintering in steel industry and remove methylene blue by synergistic activation of H3PO4 and ZnCl2. (15th March 2023) - Zhang, Yu; Shen, Boxiong; Sajjad Ahmad, Muhammad; Zhou, Wenjun; Khalid, Rana Rehan; Ibrahim, Muhammad; Bokhari, Awais
Highlights: Textile derived carbon DCM is a potential biochar for steel sintering process. Textile derived carbon DCM possessed a high methylene blue adsorption at 576 mg/g. DCM had three-dimensional structure with high effect pore volume distribution (VM/VT = 0.951) The synergy of H3 PO4 and ZnCl2 made the functional groups of P and Zn enhanced on carbon surface compared with H3 PO4 or ZnCl2 alone although the dosage halved for DCM. Physisorption-chemisorption of methylene blue occurred on the surface of DCM. Abstract: In the context of treating waste with waste, the development of three-dimensional biochar that may be used for sintering in the steel sector as well as successfully removing methylene blue from waste water is effective. The biochar activated by H3 PO4 alone (DCP), ZnCl2 alone (DCZ) and H3 PO4 cooperated with ZnCl2 (DCM) were prepared to investigate the mechanism of the synergism of H3 PO4 and ZnCl2 at pyrolysis temperature 500 °C (selecting from 300 °C to 1000 °C). The SEM analysis indicates DCM possesses a stereoscopic porous network comparing agglomeration and stacking of the others, and the SEM and BET analysis indicate that DCM possesses a stereoscopic porous network and higher effective pore volume (VM/VT = 0.951) than DCP (VM/VT = 0.584) and DCZ (VM/VT = 0.812). EDS, XPS and FTIR analysis revealed that the surface heteroatom of P and Zn enhanced on DCM compared with that of DCP (P weight%=6.39 vs 3.26) and DCZ (Zn weight% = 5.93 vs 1.85) although the activator dosage was halved for DCM. The methylene blue isotherm adsorption curve of DCM fits well with Freundlich and Dual Langmuir adsorption isotherms, the adsorption kinetics is in line with the pseudo-second-order kinetic model. The results indicate that the adsorption process is based on a heterogeneous multilayer, that physisorption-chemisorption adsorption is the primary adsorption mechanism, and that the adsorption process is regulated by the combination of intra-particle and film diffusion. The DCM demonstrates to be a promising adsorbent for methylene blue removal, performing a high removal capacity at 576 mg/g. In this study, a feasible method to synergistically activate biochar from textile wastes was proposed, to deal with the removal of methylene blue.